Ignition and flame propagation behaviors of titanium alloys in oxygen-enriched atmospheres - Congzhen Wang; Jianjun Li; Yajun Li; Guangyu He; Jinfeng Huang; Cheng Zhang (Journal of Materials Research and Technology)
Titanium and its alloys are promising structural materials for advanced aircraft engine applications. However, they are susceptible to ignition and combustion because of their active chemical performance, high combustion heat, and poor heat conductivity. In this study, the ignition and flame propagation behaviors of Ti, TC4 (Ti–6Al–4V), TC11 (Ti-6.5Al-3.5Mo-1.5Zr-0.3Si), and TC17 (Ti–5Al–2Sn–2Zr–4Mo–4Cr) alloys were systematically investigated and compared using promoted ignition-combustion tests in oxygen-enriched environments. The results show that the ignition phenomenon of the four titanium alloys all involve a sharp increase in temperature, explosive melting, and visible light. Nevertheless, the ignition temperature, maximum temperature and molten pool temperature follow the order as TC17>TC11>TC4>Ti. The critical pressures of the four alloys increases with increasing sample size and decreasing oxygen concentration, whereas ignition temperature of the four alloys decreases with increasing oxygen pressure. The activation energy for ignition of the four alloys are determined, and the difference in the activation energy for ignition among the four alloys is very slight. Assessment of the relevant burning kinetics reveal that the burning velocity for the four alloys increases with increasing oxygen pressure. The activation energy for combustion of Ti, TC4, TC11, and TC17 alloys are determined to be 131.20 kJ mol−1, 136.57 kJ mol−1, 150.56 kJ mol−1, and 100.19 kJ mol−1 respectively by fitting the relationship between oxygen pressure and molten pool temperature. Furthermore, the effects of alloy elements on ignition critical conditions, and the burning kinetics controlled by the melting point of solid-liquid interface and activation energy for combustion are discussed.